Impacts of Pig Slurry Applied to Two Different Soils on Nutrient Transport by Runoff - Danieli Schneiders Kaufmann; Ildegardis Bertol; Maria Aparecida do Nascimento dos Santos; Barbara Bagio; José Mecabô Júnior; Heinz Borg (Revista Brasileira de Ciência do Solo, 2019)
Runoff in agricultural areas with intensive application of pig slurry can transport significant amounts of nutrients. This study evaluates the effects of different pig slurry (PS) application rates (0, 50, 100, and 200 m3 ha-1) on nutrient loss through runoff during soybean cultivation under no-tillage. It was conducted at two sites in southern Brazil, one on an Alfisol (27° 43' south and 50° 3' west) and one on an Inceptisol (27° 47' south and 50° 18' west). The PS was applied to the soil once at the beginning of the soybean cycle. Each plot was 11 m long in the direction of the slope and 3.5 m wide. To induce runoff, artificial rainfall was applied in four different tests (T1, T2, T3, T4), with an intensity of 65 mm h-1 for 90 minutes. The first test was performed one day after PS application, while the other tests were performed throughout the soybean cycle. During each test, runoff samples were collected at 10-min intervals after the beginning of runoff. The runoff amount and the NO3-, NH4+, P, and K+ concentrations in the runoff were measured. In T1, nutrient transport from the Alfisol and the Inceptisol increased with increasing PS doses. In some cases, this effect was still noticeable in T2 and T3, but not in the last test (T4). The transported amounts of NO3-, NH4+, P, and K+ decreased as the period between PS application and simulated rainfall increased. Regardless of the soil and the treatment, NO3- was transported in the greatest quantities, followed by K+, NH4+, and P.